Necroptotic astrocytes contribute to maintaining stemness of disseminated medulloblastoma through CCL2 secretion. Issue 5 (15th November 2019) - Liu, Hailong; Sun, Youliang; O'Brien, Jenny A; Franco-Barraza, Janusz; Qi, Xueling; Yuan, Hongyu; Jin, Wei; Zhang, Junping; Gu, Chunyu; Zhao, Zhenyu; Yu, Chunjiang; Feng, Shiyu; et al.
Abstract: Background: Medulloblastoma (MB) with metastases at diagnosis and recurrence correlates with poor prognosis. Unfortunately, the molecular mechanism underlying metastases growth has received less attention than primary therapy-naïve MB. Though astrocytes have been frequently detected in brain tumors, their roles in regulating the stemness properties of MB stem-like cells (MBSCs) in disseminated lesions remain elusive. Methods: Effects of tumor-associated astrocyte (TAA)–secreted chemokine C-C ligand 2 (CCL2) on MBSC self-renewal was determined by immunostaining analysis. Necroptosis of TAA was examined by measuring necrosome activity. Alterations in Notch signaling were examined after inhibition of CCL2. Progression of MBSC-derived tumors was evaluated after pharmaceutical blockage of necroptosis. Results: TAA, as the essential components of disseminated tumor, produced high levels of CCL2 to shape the inflammation microenvironment, which stimulated the enrichment of MBSCs in disseminated MB. In particular, CCL2 played a pivotal role in maintaining stem-like properties via Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3)–mediated activation of Notch signaling. Loss of CCL2/C-C chemokine receptor 2 (CCR2) function repressed the JAK2/STAT3-Notch pathway and impaired MBSC proliferation, leading to a dramatic reduction of stemness, tumorigenicity, and metastasizing capability. Furthermore, necroptosis-induced CCL2 release depended on activation of receptor-interacting protein 1 (RIP1)/RIP3/ mixed lineage kinase domain-like pseudokinase (MLKL) in TAA, which promoted the oncogenic phenotype. Blockade of necroptosis resulted in CCL2 deprivation and compromised MBSC self-proliferation, indicating MBSCs outsourced CCL2 from necroptotic TAA. Finally, CCL2 was upregulated in high-risk stages of MB, further supporting its value as a prognostic indicator. Conclusion: These findings highlighted the critical role of CCL2/CCR2 in Notch signaling activation in MBSCs and revealed a necroptosis-associated glial cytokine microenvironment driving stemness maintenance in disseminations. Key Points 1. TAA-derived CCL2 promoted stemness in disseminated MBSCs through Notch signaling activation via the JAK2/STAT3 pathway. 2. TAA released CCL2 in a RIP1/RIP3/MLKL-dependent manner leading to necroptosis.